Assessment of selected metal trace elements from industrial activities in the agricultural surface soil of Menzel Bourguiba (Tunisia). Issue 4 (2nd October 2018) - Chouaieb, Leila; Hatira, Abdessatar; Gabteni, Noureddine
Abstract: In this article, we assess the levels of nickel (Ni), chromium (Cr), copper (Cu), lead (Pb), cadmium (Cd), zinc (Zn), and iron (Fe) in 28 soil surface samples around Elfouledh Iron and Steel Factory, the old discharge area and the wastewater treatment plant (domestic wastewater treatment) which are considered the direct discharge sources of various types of waste into the soil. The concentrations of these metal trace elements (MTEs) were 678 mg/kg for Pb, 447 mg/kg for Zn, 435 mg/kg for Ni, 181 mg/kg for Cr, 27, 106 mg/kg for Fe, 645 mg/kg for Cu, and 2.225 mg/kg for Cd. In fact, in many sampling points, the concentration of MTEs was higher than the critical values of the AFNOR U44041 soil quality standard, especially those collected near the industrial facilities. The principal component analysis revealed two possible anthropogenic origins for the MTEs in the soil: industrial (Fe, Pb, Zn, Cu, Cr, and Ni) and agricultural activities (Cd). The values of the pollution index (PI) and the geoaccumulation index (Igeo) indicate that these soils are deeply contaminated with these trace elements. Accordingly, these results show that installing industrial facilities near agricultural zones could have serious and damaging effects on the soil. Metals resulting from industrial activities can affect soils, water sources and thus the environment and human health. Overall, this study provides a broad understanding that will help take active measures in terms of environmental protection.